Evaluating the Effectiveness of Hydraulic Submersible Pump in Fluid Transport Application - KHAN, ASLAM; Saifulnizan Jamian (Research Progress in Mechanical and Manufacturing Engineering, 2026)
The hydraulic performance of hydraulic submersible pumps (HSPs) is evaluated in this work using Computational Fluid Dynamics (CFD) models, with an emphasis on optimising impeller design.  HSPs are essential in sectors including mining, construction, and flood control, yet they are often hampered by problems like high energy consumption and ineffective operation brought on by subpar impeller design.  Four impeller configurations which are 7-Blade 20°, 7-Blade 40°, 8-Blade 20°, and 8-Blade 40° are assessed in the study using variables such energy consumption, fluid flow, angles, pressure distribution, and blade count.  According to the results, the 7-Blade 20° impeller uses the least amount of energy and provides steady flow at a maximum speed of 6.80 m/s, making it perfect for low-pressure applications.  At the price of efficiency, the 7-Blade 40° impeller is appropriate for high-pressure applications because of its higher velocity of 8.04 m/s, which produces instability but increases pressure.  The 8-Blade 20° impeller is best suited for moderate pressure because it strikes a compromise between stability and velocity, maintaining 6.80 m/s.  The 8-Blade 40° impeller, which can achieve a speed of 8.71 m/s, provides the maximum pressure but is best suited for high-head, high-flow situations due to its greater energy consumption and turbulence.  The 8-Blade 20° impeller offers the best trade-off between energy economy and performance among them.  These results highlight how crucial it is to optimise impeller design for improved pump reliability, efficiency, and lower operating costs in industrial settings.